Chlorination of Phosphane Selenides12. Issue 14 (30th September 2014) - Upmann, Daniel; Jones, Peter G.
Abstract Chlorination of the phosphane selenide iPrtBu2PSe with PhICl2 leads to the compound iPrtBu2PSe2Cl2, which contains a P–Se–SeCl2 moiety and is formally a phosphane selenide complex of selenium dichloride. Two polymorphs of the product were identified by X‐ray structure analysis. The analogous reaction with tBu3PSe gave an oil, presumably tBu3PSe2Cl2, from which small quantities of tBu3PSe3Cl2 were obtained and characterized by X‐ray structure analysis.